Oil and the new international Economic order - The Nigerian Economic Society (Ibadan, Nigeria : University of Ibadan, 1976)
This book is a report of a conference that took place in the year 1976, the contributors includes policy makers and of course many academics. Papers presented were group in to three categories. First section contains papers on general issues of production, distribution and demand for petroleum. Second section focuses on issues relating to Nigeria. The third set are concerned with oil in international context, with emphasis on the interrelatedness, and effects of oil on the world economy.
Proceedings of the 1976 annual conference of the Nigerian Economic society.
ahz 12/04/2019
Loans
Keywords: Economy; International economic relations; Nigeria